Circulating Biomarkers in Glioblastoma: Ready for Prime Time?. Issue 5 (September 2021) - Mathios, Dimitrios; Phallen, Jillian
Abstract: Liquid biopsy approaches for detection of circulating biomarkers of cancer have been utilized in oncology in many clinical settings from early detection to disease monitoring. Recent approaches have focused on circulating tumor cells, circulating tumor DNA, and circulating RNAs in a variety of biofluids. However, very little progress has been made in implementing such approaches for detection of brain tumors, despite the tremendous clinical need for earlier and less invasive diagnosis, as well as more accurate assessment of disease status. In this review, we highlight the recent methodological improvements in the field of liquid biopsy technologies specifically for glioblastoma. Although many retrospective and few prospective studies have been conducted to assess the utility of circulating biomarkers for detection of brain tumors, none have yet moved forward to clinical implementation.